Glass Superstrate Nanoantennas for Infrared Energy Harvesting Applications - Isa Kocakarin; Korkut Yegin (International Journal of Antennas and Propagation)
Several nanoantennas for infrared energy harvesting applications at 30 THz are studied. Contrary to usual antenna designs, we implemented glass superstrate as opposed to glass substrate for better antenna performance. We defined a figure of merit (FOM) which includes antenna fractional bandwidth, peak gain, and half-power beamwidth of the antenna under consideration. Three different antenna structures with glass superstrate and one of them with glass substrate are studied in detail. According to our FOM definition, the Archimedean balanced spiral antenna exhibited superior performance among other structures with less sensitivity to the incoming polarization of the electromagnetic wave.